BIG COFFEE VL.: SEED DESICCATION TOLERANCE, SIEVE CLASSIFICATION, AND PHYSIOLOGICAL QUALITY - DE SOUZA, ANA CRISTINA; da Rosa, Sttela Dellyzete Veiga Franco; Vilela, Amanda Lima; de Figueiredo, Madeleine Alves; Vilela, Ana Luiza de Oliveira; Filho, Ricardo Stéphano; Carvalho, Milene Alves de Figueiredo (Coffee Science - ISSN 1984-3909, 2018)
A coffee plant producing large fruit, seeds, and leaves in relation to conventional coffee plants, possibly generated by genetic mutation, was named Big Coffee VL. Seeds of this coffee plant were classified by size and used to establish the crop, whose plants were designated as Big Coffee VL. large, Big Coffee VL. medium, and Big Coffee VL. small. The aim of this study was to investigate desiccation tolerance, together with size classification, and evaluate the physiological quality of the seeds of this plant. Seeds of each type of Big Coffee VL. and of the cultivar Topázio were collected. High moisture seeds and seeds dried to 11% moisture content were evaluated to assess desiccation tolerance. Dried seeds of each Big Coffee VL. progeny and of the Topázio cultivar were classified by size in sieve testing using oblong screens for separation of peaberry seeds, and circular sieves from 22 to 12 for separation of flat seeds. All seeds were subjected to physiological evaluation through the germination test and determination of seedling dry matter. A completely randomized experimental design (CRD) was used; results were subjected to analysis of variance and means compared by the Scott-Knott test. Big Coffee VL. seeds tolerate desiccation to moisture content of 11% wet basis. Seeds of the Topázio cultivar have better physiological performance than seeds of the Big Coffee VL progenies. The bigger the seeds of Big Coffee VL., the better their physiological performance, exhibiting greater seedling dry matter.